DRUG-DRUG INTERACTIONS OF THE RESERVE ANTIBIOTICS: A NARRATIVE REVIEW - Božić Cvijan, Bojana; Labović, Miljana; Kukurić, Marija; Bajčetić, Milica (Medical Research, 2024)
Drug interactions often cause side effects, especially in children, elderly and/or patients with chronic diseases. Antibiotics are among the most commonly used drugs, so potential impact of antibiotic-drug interactions on the ultimate outcome of therapy may be of great clinical value. Having in mind that antibiotic-drug interactions can lead to development of antimicrobial resistance (AMR), their identification is especially important for reserve antibiotics. The aim of this narrative review is to analyze the drug-drug interaction potential of reserve antibiotics. The highest potential for antibiotic-drug interactions was identified with linezolid, colistin, dalfopristin/quinupristin, lefamulin and oritavancin. Special caution should be paid to concomitant administration of ceftazidime-avibactam, telavancin, colistin, polymyxin B, plazomicin with drugs that have nephrotoxic potential due to possibility of more severe renal impairment.  Exceptional wariness is required when combining drugs with reserve antibiotics with limited drug-drug interactions information such as plazomicin, carumonam, iclaprim. Having in mind that antibiotic-drug interaction can lead to the changed antimicrobial efficiency and/or safety of the therapy, the antibiotic choice has to be based on data regarding interaction potential. Continuous education of clinical staff regarding the choice of antibiotics based on their interaction potential and optimizing the antibiotic dose may significantly improve pharmacotherapy and decrease the risk for AMR. Keywords: antibiotic, drug-drug interactions, reserve antibiotics, AMR.
Keywords: antibiotic, drug-drug interactions, reserve antibiotics, AMR